In the name of the people : prophets and conspirators in prerevolutionary Russia - Ulam, Adam B., 1922-2000 (New York : Viking Press, 1977)
More than a century ago, Russia saw the burgeoning of a tradition of revolutionary violence that was not to bear fruit until 1917, but that even in those earlier times deeply affected the Russian people. In this book, Adam Ulam offers a history of Russian political and intellectual life in those critical years from 1855 to 1884 and describes the successive conspiracies that shook the edifice of tsarist autocracy.
Introduction: one shot -- I. Makers of the revolutionary world. 1. Nicholas Romanov -- 2. Alexander Herzen -- 3. The New Men and Chernyshevsky -- II. A revolutionary mystery story. 4. The birth of conspiracy -- 5. Land and freedom -- 6. Nihilism -- III. The possessed. 7. Hell -- 8. The prankster -- IV. The revolutionary crusade. 9. The quiet beast -- 10. Seeds of violence -- V. The triumph of revolutionary populism. 11. The year of choice -- 12. The birth of the people's will -- 13. The elegant and slender bombs -- VI. The fall. 14. After the gallows -- 15. Epilogue.
Includes bibliographical references and index.
Donation of Anatole Shub
Keywords: Revolutionaries -- Russia -- Biography; Russia -- Politics and government -- 1855-1881.; Russia -- Intellectual life -- 1801-1917.